What’s What FSKM October/Volume 2, 2025 - UiTM, Fakulti Sains Komputer dan Matematik (Universiti Teknologi MARA, Negeri Sembilan, 2025)
A heartfelt thank you to all authors for the overwhelming support and submissions for the 2/2025 edition of What’s What FSKM. Although only 25 articles could be published due to space limitations, every contribution is truly appreciated, and more will be considered for future editions. As the official e-bulletin of Fakulti Sains Komputer & Matematik, Universiti Teknologi MARA Cawangan Negeri Sembilan, Kampus Kuala Pilah, this platform shares academic writing, creative ideas, teaching experiences, event highlights, and departmental achievements. We look forward to your continued support whether by writing, reading, or sharing and hope to see more contributions in the next edition.